Efektivitas Digitalisasi Surat Kabar di Monumen Pers Solo: Effectiveness of Newspaper Digitalization at the Press Monument Solo - Wahyu Angga Alamsyah,; Muhammad Adzan Fadhilah; Aisyah Nabilah Azhaar (Fakultas Adab dan Bahasa UIN Raden Mas Said Surakarta, 2025)
This study aims to examine the effectiveness of newspaper digitization and its application to consumers, as well as its role in preserving newspapers at the National Press Monument. Using a qualitative case study method, data were collected through interviews, observations, and documentation. The results of the study indicate that newspaper digitization has a significant impact in facilitating information access for consumers, especially the younger generation who are more accustomed to digital technology. Through platforms such as Sidak and E-Paper, the National Press Monument is able to provide newspaper archives efficiently and widely. Despite facing several challenges such as limited staff and copyright issues, digitization remains a crucial strategy in addressing the challenges of information in the digital era.